Structural and optical behavior of Ca- and Ba-doped Cu3SbS3 thin films under beta irradiation for radioluminescent nuclear battery applications - Ayar, Kevser Hisiroglu; Yagci, Ozlem; Sahiner, Eren; Icelli, Orhan (ELSEVIER, 2026)
This study demonstrates a highly radiation-tolerant Cu3SbS3 thin film system engineered through a preemptive, atomic-scale lattice-strain-compensation strategy. Synthesized via a scalable, low-temperature sol-gel method, Ca:Ba co-doped films were exposed to a 100 Gy accelerated aging dose of beta irradiation. Quantitative Rietveld analysis of X-ray diffraction data revealed that the co-doped films maintained exceptional structural integrity, exhibiting a minimal crystallinity loss of only 1.49 % compared to an 8.31 % loss in undoped films. This stability was achieved by effectively suppressing the primary radiation-induced degradation pathways, including phase segregation and amorphization, which were prevalent in the undoped material. This structural resilience was mirrored by the film's optical properties, with the co-doped material's band gap narrowing by 16 % (1.58 eV-1.33 eV), in contrast to the 35 % reduction (1.68 eV-1.10 eV) observed in its counterpart. These findings validate preemptive, atomic-scale lattice-strain-compensation, confirmed by the restoration of the host lattice parameter through the opposing strain fields of Ca2+ and Ba2+ ions. This rational design principle establishes Ca:Ba co-doped Cu3SbS3 as a non-toxic, intrinsically radiation-hardened candidate for next-generation applications such as radioluminescent nuclear batteries and space electronics.
Keywords: Cu(3)SbS(3 )thin films; Ca:Ba co-doping; Radioluminescent nuclear cells; Sol-gel; Beta-radiation; OPPORTUNITIES; Physics